Actual problems of management of production costs - Strashynska, Larysa (My University, 2020)
The problem of cost management at the enterprise is considered and the essence of the concept "cost management system" is defined. Its components are considered and the main problems of implementation are outlined. Measures to create an effective system of production cost management are substantiated. Розглянуто проблему управління витратами на підприємстві та визначено сутність поняття «система управління витратами». Розглянуто її складові та окреслено основні проблеми впровадження. Обґрунтовано заходи щодо створення ефективної системи управління витратами на виробництві.
Keywords: кафедра маркетингу; profit maximization; management system; production costs; lower prices; financial result; cost accounting system; максимізація прибутку; система управління; виробничі витрати; зниження цін; фінансовий результат; система обліку витрат